Hupa materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986
Three items relating to the Hupa language have been identified in the C. F. Voegelin Papers. All are in Subcollection II. They include Hupa material in a folder labeled "Athabascan (Chipewyan)" as well as a separate Hupa folder in Series II. Research Notes, Subseries II. Na-Dene; and Hupa examples in a comparative vocabulary of California tribes (with words from from Hupa, Wiyot, Karuk, Shasta, Achumawi, Atsugewi, Konkow, Yana, Wintu, Maidu, and Modoc) in Series II. Research Notes, Subseries V. Hokan.